Development of a Computer Program for Calculation of the Alpha Parameter in the Linear Amplitude Sweep Test and Comparison with Rheological Parameters. Issue 7 (July 2020) - Abdollahi, Seyed Farhad; Farrokhi, Mehdi; Tabatabaee, Nader
Characterizing and modeling the fatigue performance of an asphalt binder is important when designing asphalt mixtures which can resist premature fatigue failure. Performance grading (PG) standards include the fatigue factor ( G*.sinδ ) to evaluate the fatigue resistance of asphalt binders. This criterion seems to be inaccurate, especially when applied to modified asphalt binders. American Association of State Highway and Transportation Officials (AASHTO) TP 101 has been designed to evaluate the fatigue resistance of asphalt binders using Schapery's work potential theory. The damage evolution rate ( α parameter) is the key element of this method and is calculated from the rheological properties of the undamaged asphalt binder using the slope of the relaxation modulus versus the time on the log-log scale. Owing to the difficulties of conducting the relaxation test, the relaxation modulus is usually obtained using conversion methods. However, AASHTO TP 101 uses a simplified indirect method to calculate α . The present study developed a computer program called RheoSUT with which to construct relaxation master curves using different methods. The relaxation master curves of 27 asphalt binders were evaluated for estimation of the value of α . The results indicated that AASHTO TP 101 yields higher values of α . The results of the sensitivity analysis show that overestimation of α will result in up to about 200% error in the estimation of the fatigue life ( Nf ). It is also shown that binder aging and styrene-butadiene-styrene (SBS) modification directly affected the rheological parameters and relaxation master curves. Finally, it is recommended to use the relaxation-master curved based methods of calculation of α instead of the storage-modulus based ones.